Laparoskopická totální gastrektomie--nase první zkusenosti - Dostalík, J; Martínek, L; Satinský, I; Richter, V; Stigler, J (Rozhledy v chirurgii, 2003)
The advantages of mini-invasive procedures have been demonstrated in various surgical interventions. The aim of the authors was to describe, on the basis of their own experience obtained in a group of seven patients, the operation procedure of laparoscopic total gastrectomy, to discuss the advantages and to present their initial experience.
Keywords: senioři; Stomach Neoplasms; Aged, 80 and over; Middle Aged; mužské pohlaví; Laparoscopy; ženské pohlaví; gastrektomie; Humans; senioři nad 80 let; nádory žaludku; Aged; laparoskopie; Female; Gastrectomy; lidé; Male; lidé středního věku